Community perceptions about online buying and buying from an islamic economic perspective - Abdul Hamid (International Journal on Social Science, Economics and Art, 2023)
This research aims to find out how people perceive online buying and selling from an Islamic economic perspective in Ujung Bulu Village, Ujung District and what online buying and selling is like from an Islamic economic perspective in Ujung Bulu Village, Ujung District. In this study, the research subjects were people who bought and sold online on Facebook applications in Ujung Bulu Village, Ujung District. Meanwhile, the object of the research is the public's perception of online buying and selling from an Islamic economic perspective in Ujung Bulu Village, Ujung District, Parepare City. his type of research is research using descriptive qualitative methods. The research period was carried out for three months using data collection methods by means of interviews and documentation. The results of data analysis show that public perception responds very well to online buying and selling because it can help the economy and make buying and selling activities easier. The factors that influence people's perceptions about online buying and selling from an Islamic economic perspective in Ujung Bulu Village, Ujung District are; firstly, the public believes that online buying and selling does not violate religious laws, secondly there is convenience in online buying and selling, thirdly it really saves time in online buying and selling, fourthly it does not interfere with main work